Adsorbing material as well as preparation method and application thereof

By modifying the oxides of amino groups and doping nitrogen and fluorine, adsorption materials with three-dimensional ordered macroporous structures were prepared, which solved the problems of poor adsorption effect of existing adsorbents on fluorine and narrow pH application range, and achieved the effect of efficiently removing fluorine-containing wastewater.

CN119588315AActive Publication Date: 2025-03-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311166874.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-11
Publication Date
2025-03-11
Estimated Expiration
2043-09-11

AI Technical Summary

Technical Problem

The existing adsorbents have poor adsorption effect on fluorine, and have a narrow range of pH application, making it difficult to effectively remove water bodies containing excessive fluorine ions.

Method used

The amino-modified oxide is used as the adsorption material, with a three-dimensional ordered macroporous structure, doped with nitrogen and/or fluorine, and the interaction force with fluorine is enhanced through chemical modification.

Benefits of technology

The adsorption capacity and adsorption capacity of adsorbent materials to fluorine are improved, and the pH application scope is expanded, so that adsorbent materials can exhibit high efficiency and stability when treating fluorine-containing wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588315A_ABST
    Figure CN119588315A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of environmental protection, and discloses an adsorption material and a preparation method and application thereof.The adsorption material is an amino-modified oxide and is of a three-dimensional ordered macroporous structure, the amino-modified oxide is doped with nitrogen and / or fluorine, and the oxide is selected from any one of aluminum oxide, titanium dioxide and manganese dioxide. The adsorbing material disclosed by the invention has a three-dimensional ordered macroporous structure, so that fluorine ions or perfluorinated compounds in a water body can flow and contact in pore channels of the adsorbing material, and the saturated adsorbing capacity of the adsorbing material can be further improved; meanwhile, the oxide is modified by amino, and the interaction force between the oxide material and fluorine can be effectively enhanced, so that the obtained adsorption material has high adsorption capacity and selectivity on fluorine; in addition, the adsorption material is doped with nitrogen and / or fluorine, so that metal defect sites in the adsorption material can be increased, and the adsorption capacity to fluorine is further improved by utilizing the metal defect sites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of environmental protection technology, and in particular to an adsorption material and a preparation method and application thereof. Background Art

[0002] The toxicity of fluoride is related to its reactivity and structure. Soluble fluoride, such as sodium fluoride (NaF), has a certain degree of toxicity. Drinking drinking water containing excessive fluoride ions will pose a threat to human health. Cumulative fluoride poisoning such as dental fluorosis and skeletal fluorosis caused by long-term drinking of high-fluoride water is the most widespread endemic disease in the world. Excessive fluoride intake also has a significant impact on children's IQ. In addition, perfluorooctane sulfonate (PFOS), as a typical representative of perfluorinated compounds (PFCs), has the characteristics of persistence, bioaccumulation, developmental toxicity and endocrine toxicity, and poses serious ecological hazards and environmental pollution problems.

[0003] At present, the commonly used methods for fluoride removal include precipitation, ion exchange, reverse osmosis, adsorption, etc. Among them, adsorption is the most commonly used method for removing fluoride from wastewater due to its simple process, low cost and high removal efficiency. Commonly used adsorbents include activated carbon, alumina, layered double hydrotalcite, zeolite and bentonite, but so far, these adsorption materials still have some application problems. Taking activated carbon as an example, the interaction between activated carbon and fluorine is weak, resulting in its poor ability to adsorb fluorine; taking alumina as an example, the adsorption capacity of alumina is low, and the acid and alkali resistance of alumina is poor, resulting in a narrow pH range of its applicable solution. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of poor adsorption effect of traditional adsorbents on fluorine and narrow pH application range in the prior art, and to provide an adsorbent material and its preparation method and application. The adsorbent material has high adsorption capacity and strong adsorption ability for fluorine, and has a wide pH application range and is easy to regenerate.

[0005] In order to achieve the above-mentioned purpose, the present invention provides an adsorption material on the one hand, which is an amino-modified oxide having a three-dimensional ordered macroporous structure, wherein the amino-modified oxide is doped with nitrogen and / or fluorine, and the oxide is selected from any one of aluminum oxide, titanium dioxide and manganese dioxide.

[0006] Preferably, the pore size of the three-dimensional ordered macropores of the adsorption material is 250 to 400 nm, preferably 300 to 370 nm.

[0007] Preferably, the macropores of the adsorption material are connected by pore windows with a diameter of 80 to 100 nm.

[0008] A second aspect of the present invention provides a method for preparing an adsorbent material, the method comprising the following steps:

[0009] (1) centrifuging an emulsion containing polymethyl methacrylate microspheres, removing the supernatant, and obtaining a colloidal crystal template;

[0010] (2) mixing a metal precursor, citric acid, ethanol and substance A to obtain a mixed solution;

[0011] (3) immersing the colloidal crystal template in the mixed solution, and then filtering, drying and calcining to obtain an oxide having a three-dimensional ordered macroporous structure;

[0012] (4) aminated the oxide to obtain an adsorption material;

[0013] Wherein, in step (2), the metal precursor is an aluminum source, a titanium source or a manganese source, and the substance A is hydrofluoric acid and / or ammonia water.

[0014] Preferably, the method further comprises preparing an emulsion containing polymethyl methacrylate microspheres according to the following steps.

[0015] In an argon atmosphere, deionized water is heated to 70-90° C., and then mixed with methyl methacrylate monomer to obtain a mixed solution;

[0016] The mixed solution is mixed with an initiator and reacted.

[0017] Preferably, the volume ratio of the mass of the methyl methacrylate monomer to the deionized water is 100 g: 100-800 mL.

[0018] Preferably, the weight ratio of the methyl methacrylate monomer to the initiator is 100:0.3-2.

[0019] Preferably, the initiator is potassium persulfate.

[0020] Preferably, in step (1), the centrifugal speed is 2500-3500 rpm and the time is 3-12 hours.

[0021] Preferably, in step (2), the weight ratio of the metal precursor, citric acid, ethanol and substance A is 1:0.05-0.2:5-20:0.01-0.30.

[0022] Preferably, in step (2), the nitrogen source is aqueous ammonia and / or urea.

[0023] Preferably, in step (2), the aluminum source is selected from one or more of aluminum chloride, aluminum isopropoxide and aluminum nitrate.

[0024] Preferably, in step (2), the titanium source is tetrabutyl titanate and / or titanium chloride.

[0025] Preferably, in step (2), the manganese source is manganese chloride and / or manganese nitrate.

[0026] Preferably, in step (3), the immersion time is 30 to 90 minutes.

[0027] Preferably, in step (3), the drying temperature is 40 to 60° C. and the drying time is 30 to 55 hours.

[0028] Preferably, in step (3), the calcination operating conditions include: a heating rate of 0.5 to 3° C. / min, a calcination temperature of 500 to 600° C., and a calcination time of 4 to 10 h.

[0029] Preferably, in step (3), the calcination process comprises: heating the dried product to 300-330°C at a rate of 0.5-3°C and maintaining the temperature for 0-4h, and then continuing to heat the dried product to 500-600°C and maintaining the temperature for 4-10h.

[0030] Preferably, in step (4), the amino modification process comprises: mixing the oxide and toluene, then adding an organic amine and reacting, followed by centrifugation, washing and drying.

[0031] Preferably, the usage ratio of the oxide, the organic amine and toluene is 1 g: 0.1-0.5 mL: 50-200 mL.

[0032] Preferably, the organic amine is selected from one or more of 3-aminopropyltriethoxysilane, diethylenetriamine, triethylenetetramine and polydopamine.

[0033] Preferably, the reaction temperature is 100-150° C., and the reaction time is 10-20 h.

[0034] The third aspect of the present invention provides an adsorption material obtained by the method as described above.

[0035] A fourth aspect of the present invention provides a use of the adsorption material as described above in treating fluoride-containing wastewater.

[0036] In the present invention, the adsorbent material has a three-dimensional ordered macroporous structure, and the three-dimensional ordered macroporous structure material has a uniform and regular pore structure, and has a large pore size and specific surface area, which is conducive to the flow and contact of fluoride ions or perfluorinated compounds (PFCs) in its pores, and thus is conducive to increasing the saturated adsorption capacity of the adsorbent material; at the same time, by amino-modifying the oxide, not only can the interaction between the oxide material and fluorine be effectively enhanced, so that the obtained adsorbent material has a high adsorption capacity for fluorine, but also the pH application range of the obtained adsorbent material is wide; in addition, the adsorbent material is doped with nitrogen and / or fluorine, which can increase the metal defect sites in the adsorbent material, and use the metal defect sites to further increase the adsorption capacity for fluorine. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 is a TEM image of the adsorbent material prepared in Example 1 of the present invention;

[0038] Figure 2 This is a TEM image of the adsorbent material prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0039] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0040] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0041] The present invention provides an adsorption material, which is an amino-modified oxide having a three-dimensional ordered macroporous structure, wherein the amino-modified oxide is doped with nitrogen and / or fluorine, and the oxide is selected from any one of aluminum oxide, titanium dioxide and manganese dioxide.

[0042] In the present invention, by chemically modifying the oxide surface and grafting amino functional groups, the interaction between the oxide material and fluorine can be effectively enhanced, the adsorption capacity of fluorine can be improved, and the obtained adsorption material has a high adsorption capacity of fluorine.

[0043] In the present invention, the adsorption material is doped with nitrogen and / or fluorine, which can increase the metal defect sites in the adsorption material, and utilize the metal defect sites to further increase the adsorption capacity of fluorine.

[0044] The adsorption material provided by the present invention has a wide pH range. It is speculated that this may be because amino groups are distributed on the surface of the adsorption material, which can directionally adsorb fluoride ion groups by electronic interaction, so that its adsorption capacity is not affected by the pH value of the solution.

[0045] The adsorbent material of the present invention can be recycled after being regenerated using an eluent (such as sodium hydroxide, sodium carbonate and sodium bicarbonate solution). Specifically, the regeneration process of the adsorbent material is actually the process of adsorbing F - The reverse reaction is that the F adsorbed on the surface and inside the pores of the adsorbent material - Ion exchange reaction occurs again with the anions in the eluent, so that the active sites of the adsorbent material can be restored and then recycled.

[0046] In a specific embodiment, the pore size of the three-dimensional ordered macropores of the adsorption material is 250 to 400 nm, preferably 300 to 370 nm.

[0047] In a specific embodiment, the macropores of the adsorbent material are connected by pore windows with a diameter of 80-100 nm, and the existence of the pore windows forms a three-dimensional interpenetrating topological structure between the pores. Preferably, the diameter of the pore windows is 85-95 nm.

[0048] The present invention also provides a method for preparing an adsorbent material, the method comprising the following steps:

[0049] (1) centrifuging an emulsion containing polymethyl methacrylate microspheres, removing the supernatant, and obtaining a colloidal crystal template;

[0050] (2) mixing a metal precursor, citric acid, ethanol and substance A to obtain a mixed solution;

[0051] (3) immersing the colloidal crystal template in the mixed solution, and then filtering, drying and calcining to obtain an oxide having a three-dimensional ordered macroporous structure;

[0052] (4) aminated the oxide to obtain an adsorption material;

[0053] Wherein, in step (2), the metal precursor is an aluminum source, a titanium source or a manganese source, and the substance A is hydrofluoric acid and / or a nitrogen source.

[0054] Furthermore, the aluminum source is selected from one or more of aluminum chloride, aluminum isopropoxide and aluminum nitrate; the titanium source is tetrabutyl titanate and / or titanium chloride; and the manganese source is manganese chloride and / or manganese nitrate.

[0055] The method disclosed in the present invention uses polymethyl methacrylate microspheres as colloidal crystal templates, impregnates the templates with a mixed solution containing metal precursors, fills the precursors into the template gaps, and after the material is solidified, removes the template by calcination to obtain an oxide material with a three-dimensional ordered macroporous structure, and then amino modification is performed on the surface of the oxide material to obtain an adsorption material.

[0056] The method of the present invention can facilitate the flow and contact of fluoride ions or perfluorinated compounds (PFCs) in water within the pores of the adsorbent material by preparing the adsorbent material into a three-dimensional ordered macroporous structure, thereby facilitating the improvement of the saturated adsorption capacity of the adsorbent material; and can effectively enhance the interaction between the oxide and fluorine by chemically modifying the surface of the oxide having the three-dimensional ordered macroporous material and grafting amino functional groups thereon, thereby improving the adsorption capacity of the oxide for fluorine.

[0057] The method of the present invention, by adding hydrofluoric acid and / or a nitrogen source to the mixed solution, makes the obtained adsorbent material doped with nitrogen and / or fluorine, can increase the metal defect sites in the adsorbent material, and utilize the metal defect sites to further increase the adsorption capacity of fluorine. Wherein, the nitrogen source is urea and / or ammonia water.

[0058] The adsorption material prepared by the method described in the present invention has a wide pH range; in addition, the adsorption material prepared by the method described in the present invention can be recycled after being regenerated using an eluent (such as sodium hydroxide, sodium carbonate and sodium bicarbonate solution, etc.).

[0059] The method of the present invention adopts an in-situ synthesis method to nitrogen-dope or fluorine-dope the oxide. The in-situ synthesis method refers to adding an active component (nitrogen or fluorine) to a reaction system during the synthesis of the oxide, and loading the active substance onto the oxide material while the oxide is formed. By adopting the in-situ synthesis method, the interaction force between the oxide and the active component in the obtained adsorption material is relatively large, mainly because the heteroatoms occupy the lattice position in the oxide crystal, are not easy to fall off during the adsorption process, and have little effect on the pore structure of the oxide.

[0060] It should be noted that the present invention does not limit the specific order of step (1) and step (2). In other embodiments of the present invention, step (2) may also be performed before step (1), or step (2) and step (1) may be performed simultaneously. It is only necessary to complete the preparation of the colloidal crystal template and the mixed solution separately before the next operation (i.e., before step (3)).

[0061] The present invention does not limit the specific source of the emulsion containing polymethyl methacrylate microspheres in step (1), which can be prepared according to conventional methods in the art. In order to make the polymethyl methacrylate microspheres in the emulsion containing polymethyl methacrylate microspheres monodisperse and uniform in particle size, the present invention adopts soap-free emulsion polymerization to prepare them. In a preferred embodiment, the emulsion containing polymethyl methacrylate microspheres is prepared according to the following process:

[0062] Step A1, in an argon atmosphere, heating deionized water to 70-90° C., and then mixing with methyl methacrylate (MMA) monomer to obtain a mixed solution;

[0063] Step A2: mixing the mixed solution with an initiator and reacting them.

[0064] In the method of the present invention, the volume ratio of the mass of the methyl methacrylate monomer to the deionized water is 100g:100-800mL.

[0065] In the method described in the present invention, the weight ratio of the methyl methacrylate monomer to the initiator is 100:0.3-2, preferably 100:0.4-1, specifically, for example, it can be 100:0.4, 100:0.465, 100:0.5, 100:0.55, 100:0.6, 100:0.7, 100:0.8, 100:0.9 or 100:1.

[0066] In a preferred embodiment, the initiator is potassium persulfate. Further preferably, the initiator needs to be dissolved in deionized water before adding.

[0067] Further preferably, in the present invention, potassium persulfate needs to be pretreated before use, and the pretreatment process is as follows: potassium persulfate is dissolved in deionized water at 40°C, filtered while hot, and placed in a refrigerator for cooling, and then the precipitated solid powder is collected, and then repeatedly washed and filtered with ice water, dried, and then placed in a vacuum drying oven at 40°C for drying.

[0068] In a specific embodiment, step A1 includes: adding deionized water to a four-necked flask, adjusting the height of the mechanical stirring paddle, setting the stirring speed, and introducing argon; heating a constant temperature water bath to 70-90° C.; and then adding MMA monomer to obtain a mixed solution.

[0069] In a preferred embodiment, in step A2, the reaction time is 1 to 4 hours, specifically, for example, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours or 4 hours.

[0070] In a preferred embodiment, the reaction solution obtained in step A2 is filtered using a 0.2 μm to 0.5 μm microporous filter membrane to remove the cross-linked larger polymethyl methacrylate (PMMA) microspheres, and the obtained filtrate is an emulsion containing monodisperse PMMA microspheres.

[0071] In the method of the present invention, in step (1), the centrifugal speed is 2500-3500 rpm, preferably 2800-3200 rpm; the centrifugal time is 3-12 h, preferably 6-10 h.

[0072] In the method described in the present invention, in step (2), the weight ratio of the metal precursor, citric acid, ethanol and substance A is 1:0.05-0.2:5-20:0.01-0.30, preferably 1:0.05-0.2:8-12:0.01-0.10.

[0073] In the method of the present invention, in step (3), the immersion time is 30 to 90 minutes. By adjusting the composition ratio of the mixed solution and the immersion time, oxide materials with different nitrogen (fluorine) doping amounts can be obtained, thereby achieving effective regulation of the defect state of the adsorbed material. It is understood that the immersion time refers to the time of complete immersion, that is, the time the precursor solution remains after completely submerging the colloidal crystal template.

[0074] In a specific embodiment, the colloidal crystal template is immersed in the mixed solution under magnetic stirring conditions.

[0075] In a preferred embodiment, in step (3), the drying temperature is 40-60° C., and the drying time is 30-55 hours.

[0076] In a preferred embodiment, in step (3), the calcination process comprises: heating the dried product to 300-330°C at a rate of 0.5-3°C and maintaining the temperature for 0-4h, and then continuing to heat the dried product to 500-600°C and maintaining the temperature for 4-10h.

[0077] Further preferably, in step (3), the calcination process comprises: heating the dried product to 300-330°C at a rate of 0.5-3°C and maintaining for 1-4 hours, and then continuing to heat to 500-600°C and maintaining for 4-6 hours. In this way, the obtained adsorption material has better structural stability and is not easy to collapse.

[0078] In a preferred embodiment, in step (3), the dried product is mixed with quartz sand and placed in a quartz tube, and then air is introduced for calcination. Adding quartz sand during the calcination process can prevent sintering and facilitate uniform heating of the product.

[0079] In the method of the present invention, in step (4), the amino modification process includes: mixing the oxide and toluene, then adding an organic amine and reacting, followed by centrifugation, washing, and drying.

[0080] In a preferred embodiment, the usage ratio of the oxide, the organic amine and toluene is 1 g: 0.1-0.5 mL: 50-200 mL. By adjusting the amount of the organic amine added, the amount of amino adsorption on the surface of the adsorption material can be adjusted.

[0081] In a preferred embodiment, the organic amine is selected from one or more of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropylmethyldiethoxysilane, diethylenetriamine, triethylenetetramine and polydopamine.

[0082] In a preferred embodiment, step (4) comprises: dissolving the oxide in toluene, ultrasonically treating, then heating the oil bath to 100-150° C., adding an organic amine, then refluxing the oil bath for 10-16 hours, then centrifuging, and washing and drying the obtained solid product.

[0083] The present invention also proposes an adsorption material obtained by the above method. The specific content of the method refers to the above embodiment. Since the adsorption material adopts all the technical solutions of all the above embodiments, it at least has all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.

[0084] The present invention also proposes an application of the above-mentioned adsorption material in treating fluoride-containing wastewater. The adsorption material has high adsorption capacity, strong adsorption ability, easy regeneration, and a wide pH range, and can be well used for removing fluoride from fluoride-containing wastewater.

[0085] The present invention will be described in detail below through examples, but the protection scope of the present invention is not limited thereto.

[0086] Example 1

[0087] This example is used to illustrate the adsorption material and the preparation method thereof according to the present invention.

[0088] (1) Add 240 mL of deionized water to a four-necked flask, and introduce argon gas while stirring; heat in a constant temperature water bath to a constant temperature of 80° C., and then add 100 g of MMA monomer to obtain a mixed solution; then add 30 mL of a solution containing 0.5 g of potassium persulfate (pre-heated to the same temperature) to the mixed solution, and after reacting for 2 hours, filter the obtained milky white reaction solution using a microporous filter membrane with a pore size of 0.2 μm, and the obtained filtrate is an emulsion containing PMMA microspheres;

[0089] (2) centrifuging the emulsion containing PMMA microspheres at 3000 rpm for 10 h, discarding the supernatant, and drying at room temperature to obtain a colloidal crystal template;

[0090] (3) 10 g of aluminum chloride, 1 g of citric acid, 100 g of ethanol and 0.5 g of hydrofluoric acid were mixed to obtain a mixed solution;

[0091] (4) Immersing the colloidal crystal template in the mixed solution for 60 minutes, and after the impregnation is complete, filtering with a Buchner funnel to remove excess mixed solution; drying the obtained impregnated template in a 50°C oven for 48 hours to obtain a precursor salt complex, and mixing the complex with 20-mesh quartz sand and evenly loading it into a quartz tube, introducing air, and then heating to 310°C at a rate of 1°C / min, maintaining for 3 hours, and then continuing to heat to 550°C and maintaining at this temperature for 6 hours, and cooling naturally to obtain a fluorine-doped alumina material with a three-dimensional ordered macroporous structure;

[0092] (5) Dissolve 1 g of the fluorine-doped alumina material with the three-dimensional ordered macroporous structure in 100 mL of toluene, ultrasonicate for 30 s, then heat the oil bath to 110° C., add 0.3 mL of 3-aminopropyltriethoxysilane solvent, reflux in the oil bath for 18 h, and then centrifuge. Wash the obtained solid product with ethanol and finally dry it to obtain an amino-modified fluorine-doped alumina material, i.e., an adsorption material.

[0093] The prepared adsorbent material was tested using a transmission electron microscope (TEM). Figure 1 As shown. Figure 1 It can be seen that the adsorption material has a regular three-dimensional ordered macroporous structure, the pores are three-dimensionally orderly connected, the pore size is uniform, the pore wall thickness is uniform, and a clearly visible small pore window is displayed under each large pore. The pore size is about 350nm and the diameter of the pore window is about 90nm. The existence of the pore window forms a three-dimensional connected topological structure between the pores.

[0094] Example 2

[0095] The method described in Example 1 is used for implementation, except that step (1) comprises: adding 240 mL of deionized water into a four-necked flask, and introducing argon gas while stirring; heating in a constant temperature water bath to a constant temperature of 80° C., and then adding 130 g of MMA monomer to obtain a mixed solution; and then adding 30 mL of a solution containing 0.55 g of potassium persulfate (preheated to the same temperature) to the mixed solution, reacting for 2 h, and filtering the obtained milky white reaction solution using a microporous filter membrane with a pore size of 0.2 μm to obtain a filtrate containing PMMA microspheres.

[0096] The prepared adsorbent material was tested using a transmission electron microscope (TEM). Figure 2 As shown. Figure 2 It can be seen that the adsorption material has a regular three-dimensional ordered macroporous structure, the pores are three-dimensionally orderly connected, the pore size is uniform, the pore wall thickness is uniform, and a clearly visible small pore window is displayed under each large pore. The pore size is about 370nm and the diameter of the pore window is about 95nm. The existence of the pore window forms a three-dimensional connected topological structure between the pores.

[0097] Example 3

[0098] The method described in Example 1 is used for implementation, except that the prepared adsorption material is an amino-modified nitrogen-doped alumina material. Specifically, step (3) comprises: mixing 10 g of aluminum chloride, 1 g of citric acid, 100 g of ethanol and 0.5 g of ammonia water to obtain a mixed solution.

[0099] The prepared adsorption material was tested using a transmission electron microscope (TEM). The results showed that the adsorption material had a regular three-dimensional ordered macroporous structure, the pores were three-dimensionally orderly connected, the pore size was uniform, the pore wall thickness was uniform, and a clearly visible small pore window was displayed under each large pore. The pore size was about 350nm and the diameter of the pore window was about 90nm. The existence of the pore window formed a three-dimensional connected topological structure between the pores.

[0100] Example 4

[0101] The method described in Example 1 is followed, except that the aluminum chloride in step (3) is replaced by tetrabutyl titanate.

[0102] Example 5

[0103] The method described in Example 1 is followed, except that the aluminum chloride in step (3) is replaced by manganese nitrate.

[0104] Example 6

[0105] The method described in Example 1 is used for implementation, except that step (5) comprises: dissolving 1 g of the fluorine-doped alumina material with the three-dimensional ordered macroporous structure in 100 mL of toluene, ultrasonicating for 30 s, then heating the oil bath to 120° C., adding 0.2 mL of 3-aminopropyltrimethoxysilane, refluxing in the oil bath for 10 h, then centrifuging, washing the obtained solid product with ethanol, and finally drying to obtain an amino-modified fluorine-doped alumina material, i.e., an adsorption material.

[0106] Example 7

[0107] The method described in Example 1 is used for implementation, except that step (5) comprises: dissolving 1 g of the fluorine-doped alumina material with the three-dimensional ordered macroporous structure in 100 mL of toluene, ultrasonicating for 30 s, then heating the oil bath to 140°C, adding 0.25 mL of 3-aminopropylmethyldiethoxysilane, refluxing in the oil bath for 10 h, then centrifuging, washing the obtained solid product with ethanol, and finally drying to obtain an amino-modified fluorine-doped alumina material, i.e., an adsorption material.

[0108] Example 8

[0109] This example is used to illustrate the adsorption material and the preparation method thereof according to the present invention.

[0110] (1) Add 300 mL of deionized water to a four-necked flask, and introduce argon gas while stirring; heat in a constant temperature water bath to a constant temperature of 90° C., and then add 100 g of MMA monomer to obtain a mixed solution; then add 30 mL of a solution containing 0.5 g of potassium persulfate (pre-heated to the same temperature) to the mixed solution, and after reacting for 2 hours, filter the obtained milky white reaction solution using a microporous filter membrane with a pore size of 0.2 μm, and the obtained filtrate is an emulsion containing PMMA microspheres;

[0111] (2) centrifuging the emulsion containing PMMA microspheres at 3000 rpm for 8 h, discarding the supernatant, and drying at room temperature to obtain a colloidal crystal template;

[0112] (3) 10 g of aluminum chloride, 1.5 g of citric acid, 60 g of ethanol and 0.3 g of hydrofluoric acid were mixed to obtain a mixed solution;

[0113] (4) Immersing the colloidal crystal template in the mixed solution for 60 minutes, and after the impregnation is complete, filtering with a Buchner funnel to remove excess mixed solution; drying the obtained impregnated template in a 50°C oven for 48 hours to obtain a precursor salt complex, and mixing the complex with 20-mesh quartz sand and evenly loading it into a quartz tube, introducing air, and then heating to 320°C at a rate of 1°C / min, maintaining for 2 hours, and then continuing to heat to 520°C and maintaining at this temperature for 8 hours, and cooling naturally to obtain a fluorine-doped alumina material with a three-dimensional ordered macroporous structure;

[0114] (5) Dissolve 1 g of the fluorine-doped alumina material with the three-dimensional ordered macroporous structure in 100 mL of toluene, ultrasonicate for 30 s, then heat the oil bath to 110° C., add 0.2 mL of 3-aminopropyltriethoxysilane solvent, reflux in the oil bath for 18 h, and then centrifuge. Wash the obtained solid product with ethanol and finally dry it to obtain an amino-modified fluorine-doped alumina material, i.e., an adsorption material.

[0115] Example 9

[0116] This example is used to illustrate the adsorption material and the preparation method thereof according to the present invention.

[0117] (1) Add 240 mL of deionized water to a four-necked flask, and introduce argon gas while stirring; heat in a constant temperature water bath to a constant temperature of 80° C., and then add 100 g of MMA monomer to obtain a mixed solution; then add 30 mL of a solution containing 0.7 g of potassium persulfate (pre-heated to the same temperature) to the mixed solution, and after reacting for 2 hours, filter the obtained milky white reaction solution using a microporous filter membrane with a pore size of 0.2 μm, and the obtained filtrate is an emulsion containing PMMA microspheres;

[0118] (2) centrifuging the emulsion containing PMMA microspheres at 3000 rpm for 10 h, discarding the supernatant, and drying at room temperature to obtain a colloidal crystal template;

[0119] (3) 10 g of aluminum chloride, 1.2 g of citric acid, 60 g of ethanol and 0.5 g of hydrofluoric acid were mixed to obtain a mixed solution;

[0120] (4) Immersing the colloidal crystal template in the mixed solution for 60 minutes, and after the impregnation is complete, filtering with a Buchner funnel to remove excess mixed solution; drying the obtained impregnated template in a 50° C. oven for 48 hours to obtain a precursor salt complex, and mixing the complex with 20-mesh quartz sand evenly into a quartz tube, introducing air, and then heating to 310° C. at a rate of 1° C. / min, maintaining for 3 hours, and then continuing to heat to 570° C. and maintaining at the highest temperature for 5 hours, and cooling naturally to obtain a fluorine-doped alumina material with a three-dimensional ordered macroporous structure;

[0121] (5) Dissolve 1 g of the fluorine-doped alumina material with the three-dimensional ordered macroporous structure in 100 mL of toluene, ultrasonicate for 30 s, then heat the oil bath to 110° C., add 0.2 mL of 3-aminopropyltriethoxysilane solvent, reflux in the oil bath for 18 h, and then centrifuge. Wash the obtained solid product with ethanol and finally dry it to obtain an amino-modified fluorine-doped alumina material, i.e., an adsorption material.

[0122] Example 10

[0123] This example is used to illustrate the adsorption material and the preparation method thereof according to the present invention.

[0124] (1) Add 240 mL of deionized water to a four-necked flask, and introduce argon gas while stirring; heat in a constant temperature water bath to a constant temperature of 80° C., and then add 100 g of MMA monomer to obtain a mixed solution; then add 30 mL of a solution containing 0.6 g of potassium persulfate (pre-heated to the same temperature) to the mixed solution, and after reacting for 2 hours, filter the obtained milky white reaction solution using a microporous filter membrane with a pore size of 0.2 μm, and the obtained filtrate is an emulsion containing PMMA microspheres;

[0125] (2) centrifuging the emulsion containing PMMA microspheres at 3000 rpm for 10 h, discarding the supernatant, and drying at room temperature to obtain a colloidal crystal template;

[0126] (3) 10 g of aluminum chloride, 1 g of citric acid, 80 g of ethanol and 0.3 g of hydrofluoric acid were mixed to obtain a mixed solution;

[0127] (4) Immersing the colloidal crystal template in the mixed solution for 60 minutes, and after the impregnation is complete, filtering with a Buchner funnel to remove excess mixed solution; drying the obtained impregnated template in a 50° C. oven for 48 hours to obtain a precursor salt complex, and mixing the complex with 20-mesh quartz sand evenly into a quartz tube, introducing air, and then heating to 550° C. at a rate of 1° C. / min, maintaining at this temperature for 7 hours, and cooling naturally to obtain a fluorine-doped alumina material with a three-dimensional ordered macroporous structure;

[0128] (5) Dissolve 1 g of the fluorine-doped alumina material with the three-dimensional ordered macroporous structure in 100 mL of toluene, ultrasonicate for 30 s, then heat the oil bath to 110° C., add 0.25 mL of 3-aminopropyltriethoxysilane solvent, reflux in the oil bath for 18 h, and then centrifuge. Wash the obtained solid product with ethanol and finally dry it to obtain an amino-modified fluorine-doped alumina material, i.e., an adsorption material.

[0129] Comparative Example 1

[0130] The method described in Example 1 is used for implementation, except that the alumina material is not amino-modified, that is, the adsorption material is the fluorine-doped alumina material with a three-dimensional ordered macroporous structure obtained in step (4).

[0131] Comparative Example 2

[0132] The method described in Example 1 is used for implementation, except that the prepared adsorption material is an amino-modified aluminum oxide material, that is, hydrofluoric acid is not added in step (3).

[0133] Specifically, the preparation method of the adsorption material comprises the following steps:

[0134] (1) Add 240 mL of deionized water to a four-necked flask, and introduce argon gas while stirring; heat in a constant temperature water bath to a constant temperature of 80° C., and then add 100 g of MMA monomer to obtain a mixed solution; then add 30 mL of a solution containing 0.5 g of potassium persulfate (pre-heated to the same temperature) to the mixed solution, and after reacting for 2 hours, filter the obtained milky white reaction solution using a microporous filter membrane with a pore size of 0.2 μm, and the obtained filtrate is an emulsion containing PMMA microspheres;

[0135] (2) centrifuging the emulsion containing PMMA microspheres at 3000 rpm for 10 h, discarding the supernatant, and drying at room temperature to obtain a colloidal crystal template;

[0136] (3) 10 g of aluminum chloride, 1 g of citric acid and 100 g of ethanol were mixed to obtain a mixed solution;

[0137] (4) Immersing the colloidal crystal template in the mixed solution for 60 minutes, and after the impregnation is complete, filtering with a Buchner funnel to remove excess mixed solution; drying the obtained impregnated template in a 50° C. oven for 48 hours to obtain a precursor salt complex, and mixing the complex with 20-mesh quartz sand evenly into a quartz tube, introducing air, and then heating to 310° C. at a rate of 1° C. / min, maintaining for 3 hours, and then continuing to heat to 550° C. and maintaining at this temperature for 6 hours, and cooling naturally to obtain an alumina material with a three-dimensional ordered macroporous structure;

[0138] (5) Dissolve 1 g of the fluorine-doped alumina material with the three-dimensional ordered macroporous structure in 100 mL of toluene, ultrasonicate for 30 s, then heat the oil bath to 110° C., add 0.3 mL of 3-aminopropyltriethoxysilane solvent, reflux in the oil bath for 18 h, and then centrifuge. Wash the obtained solid product with ethanol and finally dry it to obtain an amino-modified alumina material, i.e., an adsorption material.

[0139] Comparative Example 3

[0140] (1) Dissolve 10 g of aluminum chloride, 1 g of citric acid, 100 g of ethanol and 0.5 g of hydrofluoric acid in 60 mL of deionized water, place in a constant temperature water bath at 40° C., and stir on a magnetic stirrer until uniform. Then, slowly add ammonia water to the solution to adjust the pH value of the solution to 9, and continue stirring until a gel is obtained.

[0141] (2) filtering and washing the gel, drying it in an oven at 60° C., and calcining it in a muffle furnace at 550° C. for 5 h to obtain a disordered fluorine-doped alumina material;

[0142] (3) Dissolve 1 g of the disordered fluorine-doped alumina material in 100 mL of toluene, ultrasonicate for 30 s, then heat the oil bath to 110° C., add 0.3 mL of 3-aminopropyltriethoxysilane solvent, reflux in the oil bath for 18 h, then centrifuge, wash the obtained solid product with ethanol, and finally dry it to obtain the adsorption material.

[0143] Test Example 1

[0144] The adsorption capacity of the adsorbent materials prepared in Examples 1-10 and Comparative Examples 1-3 was tested. The test method was as follows: 200 mL of an aqueous solution with a fluoride ion concentration of 20 mg / L was prepared, the pH in the system was adjusted to 6, 0.1 g of the adsorbent material was added, the mixture was stirred evenly, stirred for 2 h, the adsorbent was filtered out, and the fluoride ion concentration before and after adsorption was measured using an inductively coupled plasma spectrometer. The fluoride ion adsorption amount was calculated according to the following formula. The results are shown in Table 1.

[0145] Adsorption amount (mg / g) = (C0-C1)V / (m×1000)mg / g;

[0146] Wherein, C0 refers to the initial concentration of fluoride ions (mg / L), C1 refers to the concentration of fluoride ions after adsorption equilibrium (mg / L); V is the volume of the fluoride-containing aqueous solution (mL); and m is the dosage of the adsorbent material (g).

[0147] Table 1

[0148]

[0149]

[0150] It can be seen from Table 1 that the adsorption capacity of the adsorbent material provided by the present invention for fluoride ions can reach 33.8 mg / g, and the adsorption performance is good.

[0151] Test Example 2

[0152] The adsorbent materials prepared in Example 1 and Comparative Example 1 were tested for their fluorine adsorption performance under different pH conditions. The test method was carried out in accordance with the method described in Test Example 1, except that the pH of the fluorine-containing aqueous solution was 3, 6 and 9 respectively. The other conditions were the same: 200 mL of an aqueous solution with a fluorine ion concentration of 20 mg / L, 0.1 g of the adsorbent material was added, the mixture was stirred evenly, and stirred for 2 hours. The results are shown in Table 2.

[0153] Table 2

[0154]

[0155] It can be seen from Table 2 that the adsorption material provided by the present invention has good adsorption effect on fluorine in the pH range of 3 to 9 and has a wide pH application range.

[0156] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An adsorption material, characterized in that: The adsorption material is an amino-modified oxide having a three-dimensional ordered macroporous structure, wherein the amino-modified oxide is doped with nitrogen and / or fluorine, and the oxide is selected from any one of aluminum oxide, titanium dioxide and manganese dioxide.

2. The adsorption material according to claim 1, characterized in that The pore size of the three-dimensional ordered macropores of the adsorption material is 250-400 nm, preferably 300-370 nm.

3. The adsorption material according to claim 1, characterized in that The macropores of the adsorption material are connected by pore windows with a diameter of 80 to 100 nm.

4. A method for preparing an adsorbent material, characterized in that: The method comprises the following steps: (1) centrifuging an emulsion containing polymethyl methacrylate microspheres, removing the supernatant, and obtaining a colloidal crystal template; (2) mixing a metal precursor, citric acid, ethanol and substance A to obtain a mixed solution; (3) immersing the colloidal crystal template in the mixed solution, and then filtering, drying and calcining to obtain an oxide having a three-dimensional ordered macroporous structure; (4) aminated the oxide to obtain an adsorption material; Wherein, in step (2), the metal precursor is an aluminum source, a titanium source or a manganese source, and the substance A is hydrofluoric acid and / or a nitrogen source.

5. The method according to claim 4, characterized in that The method further comprises preparing an emulsion containing polymethyl methacrylate microspheres according to the following steps: In an argon atmosphere, deionized water is heated to 70-90° C., and then mixed with methyl methacrylate monomer to obtain a mixed solution; The mixed solution is mixed with an initiator and reacted.

6. The method according to claim 5, characterized in that The mass ratio of the methyl methacrylate monomer to the volume of deionized water is 100 g: 100-800 mL; Preferably, the weight ratio of the methyl methacrylate monomer to the initiator is 100:0.3-2; Preferably, the initiator is potassium persulfate.

7. The method according to any one of claims 4 to 6, characterized in that: In step (1), the centrifugal speed is 2500-3500 rpm and the time is 3-12 hours.

8. The method according to any one of claims 4 to 6, characterized in that: In step (2), the weight ratio of the metal precursor, citric acid, ethanol and substance A is 1: 0.05-0.2: 5-20: 0.01-0.30; Preferably, in step (2), the nitrogen source is ammonia water and / or urea; Preferably, in step (2), the aluminum source is selected from one or more of aluminum chloride, aluminum isopropoxide and aluminum nitrate; Preferably, in step (2), the titanium source is tetrabutyl titanate and / or titanium chloride; Preferably, in step (2), the manganese source is manganese chloride and / or manganese nitrate.

9. The method according to any one of claims 4 to 6, characterized in that: In step (3), the immersion time is 30 to 90 minutes; Preferably, in step (3), the drying temperature is 40 to 60° C. and the drying time is 30 to 55 hours; Preferably, in step (3), the calcination process comprises: heating the dried product to 300-330°C at a rate of 0.5-3°C and maintaining the temperature for 0-4h, and then continuing to heat the dried product to 500-600°C and maintaining the temperature for 4-10h.

10. The method according to claim 4, characterized in that In step (4), the amino modification process includes: mixing the oxide and toluene, then adding an organic amine and reacting, followed by centrifugation, washing and drying.

11. The method according to claim 10, characterized in that The usage ratio of the oxide, the organic amine and toluene is 1g: 0.1-0.5mL: 50-200mL; Preferably, the organic amine is selected from one or more of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropylmethyldiethoxysilane, diethylenetriamine, triethylenetetramine and polydopamine; Preferably, the reaction temperature is 100-150° C., and the reaction time is 10-20 h.

12. An adsorbent material obtained by the method according to any one of claims 4 to 11.

13. Use of the adsorption material according to any one of claims 1 to 3 and 12 in treating fluoride-containing wastewater.

Citation Information

Patent Citations

  • Three-dimensional ordered macroporous alumina and preparation method thereof

    CN102040235A

  • 3DOM oxide supported alkali / manganese metal oxide catalyst as well as preparation method and application thereof

    CN104475086A

  • Organic amine functionalized large-pore-volume aluminum oxide CO2 absorbent and preparation method thereof

    CN106890621A

  • Fluoride ion recovery material and its manufacturing method, and fluoride ion recovery method

    JP2005118639A

  • Wide Mesoporous Alumina Composites Having Trimodal Pore Structure

    US20090060811A1